Prevalencia y factores asociados a osteoporosis en pacientes de Santa Marta (Colombia) (2016)
Objective: To identify the prevalence and factors associated with osteoporosis in a group of patients of Santa Marta. Materials and Method: Retrospective descriptive and correlational study in a population of 406 patients from a total of 1486 consultants. Results: The prevalence found was 27.32; associated factors were: age higher than 50 years (p= 0.3405), female gender (p= 0.3405), no physical exercise (p= 0.011), parity (p= 0, 0001). Statistical association was found between osteoporosis and diseases of the eye and adnexa (p= 0.0415), by classification International Council Disease. Conclusions: The prevalence of osteoporosis was 27.32%. Age, sedentary lifestyle, multiparity, diseases of the eye and its annexes, the background to ginecobst and gallbladder surgeries were statistically significant risk factors for developing osteoporosis. © Servicio de Publicaciones - Universidad de Murcia.